Surgical treatment of macular detachment secondary to congenital pit of the optic disc: case report - Maia Júnior,Otacílio de Oliveira (2008)
The authors describe a patient with macular detachment in the right eye, secondary to congenital pit of the optic disc, submitted to vitrectomy, drainage of the subretinal fluid, perfluorocarbon, endolaser and perfluoropropane gas (C3F8). A sample of the vitreous humor was taken for comparative analysis with the subretinal fluid. Results of retinography, optical coherence tomography, and illustrations of the surgical procedure are presented. Optical coherence tomography revealed the detachment resolved 6 months after surgery. Visual acuity improved from 20/400 to 20/30. This surgical technique can lead to successful reattachment of the macula and improvement of central vision. Additionally, a qualitative and comparative analysis showed a similar biochemical composition of the subretinal fluid and the vitreous. Despite technical limitations, this analysis can confirm the pathophysiology of the disease, suggesting that the subretinal fluid may originate from the vitreous cavity in macular detachment secondary to congenital pit of the optic disc.